An On‐Treatment Analysis of the MARQUIS Study: Interventions to Improve Inpatient Medication Reconciliation. Issue 10 (21st August 2019) - Mixon, Amanda S; Kripalani, Sunil; Stein, Jason; Wetterneck, Tosha B; Kaboli, Peter; Mueller, Stephanie; Burdick, Elisabeth; Nolido, Nyryan V; Labonville, Stephanie; Minahan, Jacquelyn A; Orav, E John; Goldstein, Jenna; et al.
Abstract : It is unclear which medication reconciliation interventions are most effective at reducing inpatient medication discrepancies. Five United States hospitals' interdisciplinary quality improvement (QI) teams were virtually mentored by QI‐trained physicians. Sites implemented one to seven evidence‐based interventions in 791 patients during the 25‐month implementation period. Three interventions were associated with significant decreases in potentially harmful discrepancy rates: (1) defining clinical roles and responsibilities, (2) training, and (3) hiring staff to perform discharge medication reconciliation. Two interventions were associated with significant increases in potentially harmful discrepancy rates: training staff to take medication histories and implementing a new electronic health record (EHR). Hospitals should focus first on hiring and training pharmacy staff to assist with medication reconciliation at discharge and delineating roles and responsibilities of clinical staff. We caution hospitals implementing a large vendor EHR, as medication discrepancies may increase. Finally, the effect of medication history training on discrepancies needs further study.